Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1439-0396.2006.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of essential oils from fennel (Foeniculi aetheroleum) and caraway (Carvi aetheroleum) in pigs

Abstract: The ban of antibiotics as a feed additive requires alternatives to stabilize the health and performance particularly of the young animals. Essential oils obtained from fennel seed (Foeniculi aetheroleum) and caraway seed (Carvi aetheroleum) were tested in diets for weaned piglets in comparison with either a diet without feed additive or with a combination of formic acid and copper (positive control). Four groups of sixteen piglets (live weight 7 kg, age 26 days) received diets without (1) or with supplements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 16 publications
4
35
0
4
Order By: Relevance
“…No data were found in the literature at hand on the possible effects of adding EOSk to drinking water in farm animals. Doserelated depression of palatability was reported in pigs fed essential oils from fennel and caraway, as well as from the herbs thyme and oregano (Schöne et al, 2006). Lee et al (2003) reported that inclusion of 0.2 g · kg -1 carvacrol in broiler diets resulted in a 2% increase in feed intake and average daily gain and a 1% decrease in FCR.…”
Section: Discussionmentioning
confidence: 99%
“…No data were found in the literature at hand on the possible effects of adding EOSk to drinking water in farm animals. Doserelated depression of palatability was reported in pigs fed essential oils from fennel and caraway, as well as from the herbs thyme and oregano (Schöne et al, 2006). Lee et al (2003) reported that inclusion of 0.2 g · kg -1 carvacrol in broiler diets resulted in a 2% increase in feed intake and average daily gain and a 1% decrease in FCR.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported decreased feed intake with increasing inclusion levels of the phytogenic substance used. 4,7 The addition of phytogenic feed additives to pig diets may not affect feed intake in some instances 8,9 and even resulted in better feed effi ciency in one study. 8 Increased palatability of the diets associated with the addition of phytogenics also may be due to their anti-oxidative effects, 10 which might contribute to preserving the desired organoleptic qualities of the diet.…”
Section: What Products Are Being Used As Phytogenic Feed Additives?mentioning
confidence: 99%
“…6 Organisms commonly used include Lactobacillus acidophilus, Enterococci faecium, Bacillus species, Bifi dobacterium bifi dum, and the yeast Saccharomyces cerevisiae. 7 As feed additives, they are supplemented in diets to improve the balance of bacteria in the gut. To be effective, a probiotic must have the following traits: 8…”
Section: What Are Probiotics?mentioning
confidence: 99%
“…Two methodologies exist in the feed choice tests: a one-way test in which various diets are alternatively presented, and the 'multiple-way choice test' in which two or more diets are presented simultaneously in a free-choice situation (e.g. Schö ne et al, 2006;Guillemet et al, 2007;Sola-Oriol et al, 2009). In the free-choice situation, the result does not predict the behaviour in a practical situation in which a unique food is usually supplied, whereas the oneway test allows the analysis of feeding preference, but at the same time limits the influence of alternate food resources Figure 4 Examples of the experimental cages and operating devices used to investigate the feeding behaviour and motivation in pigs.…”
mentioning
confidence: 99%
“…growth of growing pigs : Campbell, 1976;King, 1979;Lawlor et al, 2003;Edge et al, 2005;Schö ne et al, 2006;Langendijk et al, 2007;Sola-Oriol et al, 2009;or reproductive sows: Bergeron et al, 2000;Robert et al, 2002;Guillemet et al, 2006 and. Just like weaning pigs, reproductive sows have to cope with changes in their physical and social environment and modifications in their diet throughout their breeding cycle.…”
mentioning
confidence: 99%